Analysis of Asnaf Entrepreneurial Development Based on the First Principle of Islamic-based Development - Mohd Khalil, Najwa; Mohamed Saniff, Shereeza (KnE Social Sciences, 2023)
The advent of Covid-19 pandemic, which surprised the world in 2020, has increased the poverty gap worldwide. Malaysia is not spared. In Malaysia, zakat institutions endeavored to develop several poverty management programs to assist asnaf (poor and needy) in meeting their basic necessities while developing their own ability to escape the chains of poverty. Literature suggests that these asnaf are shackled in the poverty culture and requires close supervision. In the zeal of developing these asnaf as entrepreneurs to fulfill their tangible needs, they too need knowledge of their responsibilities as khalifah (caliphs) on earth. This study intends to examine asnaf entrepreneurial development from the perspective of Islamic-based development based on the first principle–tasawwur (or Islamic worldview). It seeks to identify how asnaf entrepreneurial development is associated with tasawwur as the mould to development. This concept covers three fundamental components of Islamic tasawwur. Based on the collection of secondary data through documents reviews and using content analysis, proves that developing asnaf entrepreneurs to be dynamic and pious entrepreneurs who are governed by the Quran’s teachings by emphasizing solely on tangible or material factors alone is inadequate. There needs to be concerted efforts to incorporate the three Islamic tasawwur components. The implication from the findings suggests that there is a need for zakat institutions, government agencies, NGOS, and the asnaf themselve to commit to develop asnaf entrepreneurs by incorporating these components in their poverty management strategies to ensure that the entrepreneurs that are born from such programs are materially independent, imbued with strong resilience requiring minimal supervision. Keywords: Islamic tasawwur, asnaf entrepreneurs, Islamic development principles, Islamic-based development, zakat